PERILAKU CYBERLOAFING TERHADAP KONTROL DIRI PADA PEGAWAI - Suranta, Jerri; hurriyati, Dwi (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2018)
This study was conducted to determine the relationship between self-control and cyberloafing behavior. The hypothesis proposed in this study is that there is a positive relationship between self-control and cyberloafing behavior in  staff. Subjects in this study amounted to 170 administrative employees in Palembang  Hospital. The sample technique used in this study is simple random sampling technique. The measuring instrument used is the scale of self-control and Cyberloafing behavior. The analysis technique used is simple regression using SPSS version 20.0 The results of the analysis show that the correlation coefficient (r) = 0.515 with the score obtained is (R-square) = 0.265 and p = 0.000 (p <0.05 and p <0.01) which means that the proposed hypothesis is accepted. These results indicate that there is a very significant relationship between self-control and cyberloafing behavior in administrative staff in Palembang  Hospital. The variable contribution of self-control with cyberloafing behavior variable is 26.5%.